2016
DOI: 10.1002/ecs2.1437
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of stable carbon isotopes of tissue fatty acids in Atlantic pollock (Pollachius virens)

Abstract: Abstract. Reliable estimates of diet to tissue fractionation of fatty acid (FA) stable carbon isotopes are essential for the development of techniques employing these biomarkers. In this work, Atlantic pollock (Pollachius virens) was used as a model species to investigate fractionation arising from metabolic processes during assimilation of dietary FA into serum and liver; we also examined fractionation occurring from mobilization of FA from liver during fasting. Pollock were fed diets containing FA of known i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 59 publications
(51 reference statements)
4
32
0
Order By: Relevance
“…Diet tracing methods can be also combined non-independently, where diet information from one method is being integrated with another dietary technique . Recent advances in 2011), Budge et al (2016), Gladyshev et al (2012), Gladyshev et al (2016 and isotope data (Stock & Semmens, 2015) and with other biological data (Swanson et al, 2015). For instance, using dietary estimates of visual or molecular analyses as prior information for Bayesian isotope mixing models can improve quantitative diet estimates (Chiaradia et al, 2014).…”
Section: Integration Of Multiple Dietary Methodsmentioning
confidence: 99%
“…Diet tracing methods can be also combined non-independently, where diet information from one method is being integrated with another dietary technique . Recent advances in 2011), Budge et al (2016), Gladyshev et al (2012), Gladyshev et al (2016 and isotope data (Stock & Semmens, 2015) and with other biological data (Swanson et al, 2015). For instance, using dietary estimates of visual or molecular analyses as prior information for Bayesian isotope mixing models can improve quantitative diet estimates (Chiaradia et al, 2014).…”
Section: Integration Of Multiple Dietary Methodsmentioning
confidence: 99%
“…All rights reserved. deposition in the predator, their relative amounts may be altered owing to catabolism or selective deposition and mobilization [10][11][12]. Thus, a key aspect of this approach is the adjustment of the predator's FA profile for these modifications.…”
Section: Introductionmentioning
confidence: 99%
“…In QFASA applications, these modifications are taken into account using 'calibration coefficients' (CC) [13], defined as the ratio of the proportion of a FA in the predator's tissue relative to the proportion of the same FA in diet, after feeding the diet for a prolonged period [9]. While the basic biochemical processes that may occur are well known [12], the precise changes in FA concentration that arise from metabolism remain uncertain, making empirically derived CC essential.…”
Section: Introductionmentioning
confidence: 99%
“…For tracing the dietary essential fatty acid origin, although their carbon stable isotope ratios would be helpful, information about isotopic fractionation of essential fatty acids between diet and consumers is limited. For instance, Budge et al [26] demonstrated that there was no isotopic fractionation in several essential fatty acids between the diet and serum of fish in a feeding experiment with Atlantic Pollock. Moreover, an almost isotopically unchanged transfer of 18:2ω6 and 18:3ω3 between diet and zebrafish Danio rerio was observed in a 100-day feeding experiment with constant dietary sources [27].…”
Section: Introductionmentioning
confidence: 99%